EFFECT OF JATI BELANDA LEAVES EXTRACT ON MYELOPEROXIDASE LEVEL IN WISTAR RAT'S LUNG INDUCED CONTUSION PULMONUM - Tamzil, Nia Savitri; Lusiana, Evi; Oktariana, Desi (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Pulmonary contusions are injuries to the lung parenchyma that often result from blunt trauma to the chest wall. This injury will activate the inflammatory response which can produce the effects of oxidative stress so that eventually lung damage occurs. Several studies have identified the effects of Jati Belanda leaves extracts related to the inflammatory process and their effects as antioxidants. This research is an in vivo experimental study with a prepost-test with control group design approach that aims to determine the effectiveness of the extracts of Jati Belanda (Guazuma ulmifolia) in its protection against pulmonary alveolar cells by pretreatment pulmonary contusions. The subjects of this study were white rats (Rattus norvegicus) Wistar strain which were divided into 5 groups namely positive control, negative control, Dutch teak leaf extract 125 mg / kgBB, 250 mg / kgBB and 500 mg / kgBW. Rats were induced by dropping a weight of 400 grams as high as 50 cm. The results of the study of Jati Belanda Leaf Extract (EDJB) all doses and positive control can significantly reduce levels of myeloperoxidase expression (p <0.05). Therefore, it can be concluded that the extracts of Jati Belanda leaves (Guazuma ulmifolia) are all effective doses in reducing the expression of myeloperoxidase in pulmonary tissue of Wistar rats induced by pulmonary contusions.